DEPENDENCE OF THE REPRODUCTIVE FUNCTION OF SCHOOLGIRLS AGED 12-15 YEARS FROM THEIR LIFESTYLE PECULIARITIES - A. G. Sukharev; O. A. Shelonina; L. F. Ignatova; V. V. Stan; N. M. Tsirenova ("Paediatrician" Publishers LLC, 2012)
Judging upon the results of recent studies we can state that over the past years there is a negative tendency in reproductive health of schoolgirls aged 12-15. Study objective was to evaluate dependency of reproductive function of schoolgirls from their lifestyle. A hypothesis has been stated upon presence of causal relations in the biosocial system «Health-Lifestyle» and upon necessity of healthy lifestyle motivation to preserve girl's reproductive health. 128 girls took part in the study from 5-7 forms from 2 Moscow schools. Results of the study stand for well-timed correction of the girl's lifestyles in order to prevent disorders of reproductive system.m.